Lisbon earmarking in the Polish region of Wielkopolska - does it tell the whole truth about Lisbon-oriented expenditures? - Marta Zaleska; Zbigniew Mogiła; Joanna Kudełko (European Regional Science Association (ERSA), 2013)
At the end of the 1990s, the challenges of globalization and decreasing competitiveness of the EU economy led to the implementation of a new action plan known as the Lisbon Strategy. It was aimed at improving the position of the European Union in the global economy - especially with respect to the United States. Innovations, competitiveness, dynamic knowledge-based economy, greater employment, sustainable economic growth became the main objectives of the plan. The Lisbon Strategy was modified in 2005. Nowadays it is followed by Europe 2020 - the main strategy of the EU. In order to achieve the goals of the Lisbon Strategy the European Union decided to put into force so called "earmarking" which meant dedicating Cohesion Policy funds to strengthen- among others- competitiveness, research and development activities, human capital and energy efficiency. Earmarking has created the criteria of evaluating the pro - Lisbon expenditures within the operational programmes. The main aim of this paper is to present the results of the analysis of Lisbon - oriented expenditures within the Regional Operational Programme 2007-2013 (WROP) for the Wielkopolska region in Poland. It is especially of great importance since Poland has become the largest national beneficiary of EU Cohesion Policy expenditure within the Financial Framework 2007-2013 which has created a great opportunity for the Polish regions to accelerate and improve the long-term quality of their socio-economic development. This paper will present the results of the analysis of compliance of approximately 1800 projects within WROP with the objectives of the Lisbon Strategy. Among the 33 intervention categories under the WROP, 16 were identified as those belonging to earmarking categories. The remaining 17 intervention categories were analyzed in detail in order to estimate the degree of their impact on the implementation of the Lisbon Strategy goals. The preliminary results indicate that the part of non-earmarking expenditure within WROP significantly pursues the goals of the Lisbon Strategy. It gives rise to a discussion on the rigidity of allocations of the EU funds. The conclusions might make a contribution to the debate regarding the rules of funds allocation within the Cohesion Policy in the new Financial Framework 2014-2020.
Keywords: R58; 330; earmarking; Lisbon Strategy; intervention categories; cohesion policy